Investigation Of Adhesion Between Microwave Plasma Treated Epoxy And Silicone - Choong, Lai Fan (2020)
Adhesion between silicone and microwave plasma treated epoxy in oxygen was studied. Wettability of epoxy was investigated by varying 2.45 GHz microwave plasma power (100-600 W), oxygen flow rate (20-60 sccm) and treatment time (1-5 min). Oxygen plasma activation by the microwave plasma transformed hydrophobic surface of epoxy to hydrophilic by reducing water contact angle from 102° to 14° with plasma power of 300 W in oxygen flow rate of 20 sccm for 1 min. The plasma treatment can effectively increase the oxygen-to-carbon atomic ratio of epoxy from 0.16 to 0.28, which can be attributed to polar groups including C–O, C=O and O=C–O. Root-mean-square roughness can be enhanced by 26% by exposing epoxy for 5 min at plasma power of 300 W in oxygen flow rate of 20 sccm. Based on the regression analysis, the increment in shear strength between epoxy and silicone can be related to epoxide groups (C–O–C) and low molecular weight oxidized materials (LMWOM). The beneficial effects of LMWOM on the shear strength between epoxy and silicone signifies the compatibility of LMWOM in silicone. Cross-linking of polymer chains between LMWOM and epoxy forms polymer chains with higher molecular weight which can enhance shear strength between epoxy and silicone. Transient surface properties monitoring for two months had been conducted. The instability of the surface topography of epoxy correlates well with the typical symptoms of hydrophobic recovery phenomenon. In particular, the significant increment in shear strength between aged epoxy and silicone is an important finding, which is completely contradicting with literature. The shear strength between epoxy and silicone drastically raises from zero day to one week but it gradually reduces in further aging for two months. The rise in shear strength on aged epoxy within one week is in line with the increment in epoxide groups. Further ageing from one week to two months, the gradual decline in shear strength between epoxy and silicone is due to the dominating influence of the decaying in surface free energy and oxidation state of silicon dioxide. During ageing, LMWOM play negligible role in affecting the shear strength between epoxy and silicone probably due to the consumption of LMWOM in cross-linking reactions and the diffusion of LMWOM from the surface of epoxy to the bulk. After two months, the adhesion of plasma treated epoxy sustains at a relatively high value compared to that of untreated epoxy. The shear strength between epoxy and silicone was considerably improvedout after reliability stress tests. The prolonged elevated adhesion of plasma treated epoxy and excellent reliability performance of the adhesion between epoxy and silicone, demonstrated the advantages of surface activation by 2.45 GHz microwave plasma.